Survey of Junior High School Students' Understanding of the Impacts of Early Marriage - Sabita, Fidela Yasmine; Mazza, M. Zahid; Azizah, Umi; Hartanto, Eko Budi (Universitas Negeri Malang, 2024)
UNICEF reports that the rate of child marriage in Indonesia remains high, reaching approximately 23 percent. This study employs a survey method at Junior High School (SMP Negeri 1 Dau) with a quantitative descriptive approach. Data were collected through an online questionnaire distributed to all eighth-grade students, with a sample of 57 students selected randomly. Data analysis was performed using descriptive statistics and percentages. The results indicate that the main indicators are an increased risk of domestic violence (101.16%) and significant pressure on adolescents (103.50%). Impacts on mental and emotional health, as well as personal and social development disruptions, are also of concern to students, with scores of 98.83% and 97.07%, respectively. The majority of students are aware of the negative impacts of early marriage on education (95.32%) and economic factors (97.66%). However, many students do not fully understand that early marriage can restrict career choices (93.56%) and increase physical health risks (94.73%). These findings suggest that although there is awareness of the negative impacts of early marriage, students' understanding needs to be enhanced to achieve a more comprehensive insight. Keywords: Survey; Students' Understanding; Impacts; Early Marriage